2008
DOI: 10.1002/app.27564
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of recycled poly(ethylene terephthalate)/glass fiber blends with ethylene–butyl acrylate–glycidyl methacrylate copolymer and maleic anhydride grafted polyethylene–octene rubber

Abstract: The aim of this study was to improve the toughness of recycled poly(ethylene terephthalate) (PET)/ glass fiber (GF) blends through the addition of ethylenebutyl acrylate-glycidyl methacrylate copolymer (EBAGMA) and maleic anhydride grafted polyethylene-octene (POEg-MAH) individually. The morphology and mechanical properties of the ternary blend were also examined in this study. EBAGMA was more effective in toughening recycled PET/GF blends than POE-g-MAH; this resulted from its better compatibility with PET an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…The blending of bottle-grade post-consumer polyethylene terephthalate (PET) with suitable polymers and/or compounding with SGFs can be used to attain improved properties of the post-consumer PET and broaden the possibilities for its use as an engineering thermoplastic. Cheng et al 2 studied SGF-reinforcement in blends of post-consumer PET and ethylene-butyl acrylate-glycidyl methacrylate (EBA-GMA) copolymer and of post-consumer PET and maleic anhydride grafted polyethylene-octene elastomer (POE-MAH). Karsli et al 3 investigated the effects of SGF-reinforcement on the properties of post-consumer polyethylene terephthalate/poly(ethylene naphthalate) (PET/PEN) blends.…”
Section: Introductionmentioning
confidence: 99%
“…The blending of bottle-grade post-consumer polyethylene terephthalate (PET) with suitable polymers and/or compounding with SGFs can be used to attain improved properties of the post-consumer PET and broaden the possibilities for its use as an engineering thermoplastic. Cheng et al 2 studied SGF-reinforcement in blends of post-consumer PET and ethylene-butyl acrylate-glycidyl methacrylate (EBA-GMA) copolymer and of post-consumer PET and maleic anhydride grafted polyethylene-octene elastomer (POE-MAH). Karsli et al 3 investigated the effects of SGF-reinforcement on the properties of post-consumer polyethylene terephthalate/poly(ethylene naphthalate) (PET/PEN) blends.…”
Section: Introductionmentioning
confidence: 99%
“…Besides such additives, the addition of other polymers (e. g. polyethylene, polypropylene) or inorganic materials (clay minerals) has been applied for thermomechanical PET recycling to improve mechanical properties of the recyclate [81][82][83][84][85][86][87][88][89][90][91][92][93][94]. In addition to blending PET with a second polymer, the use of compatibilizers such as ethylene vinyl acetate, ethylenebutyl acrylate-glycidyl methacrylate copolymer, poly (styrene-ethylene/butylene-styrene) and epoxy-chain extenders has been applied to further improve mechanical properties [82][83][84][85][86]. Although the use of additives to PET can improve properties of thermo-mechanically recycled PET, it ultimately leads to a downcycling of the material, since this material becomes increasingly difficult to be recycled again due to the heterogeneous and inherent composition of PET with the other components.…”
Section: Re-melting With Additivesmentioning
confidence: 99%
“…There were studies [9][10][11] using POE-g-MAH as a toughening modifier in PET systems. Chiu et al [9] revealed that the hydroxyl end group of PET may react with the anhydride group of POE-g-MAH and the formation of graft copolymers acted as compatibilizers of PET system.…”
Section: Introductionmentioning
confidence: 99%